PENDAPATAN, LITERASI KEUANGAN DAN MOTIVASI INVESTASI TERHADAP MINAT BERINVESTASI MAHASISWA STIE SATYA DHARMA SINGARAJA - Trisnadewi, Ni Kadek Ayu; Puspita Sari, Ni Komang Yunika (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the effect of income, financial literacy, and investment motivationon students' interest in investing. This research is a quantitative study using primary data obtained fromdistributing questionnaires. The population of this study were students of the Sekolah Tinggi Ilmu Ekonomi(STIE) Satya Dharma. The number of samples in this study was 120 students, sampling using a purposivesampling technique. Data analysis used multiple linear regression analysis with the help of the IMB SPSSversion 25 application. The results showed that income did not affect the investment interest of SekolahTinggi Ilmu Ekonomi (STIE) Satya Dharma students. In contrast, financial literacy and investmentmotivation positively and significantly affected the investment interest of Sekolah Tinggi Ilmu Ekonomi(STIE) Satya Dharma students.